Autonomic function in gastroparesis and chronic unexplained nausea and vomiting: Relationship with etiology, gastric emptying, and symptom severity. Issue 8 (15th February 2020) - Nguyen, Linda; Wilson, Laura A.; Miriel, Laura; Pasricha, Pankaj J.; Kuo, Braden; Hasler, William L.; McCallum, Richard W.; Sarosiek, Irene; Koch, Kenneth L.; Snape, William J.; Farrugia, Gianrico; Grover, Madhusudan; et al.
Abstract: Background: Autonomic dysfunction can be present in patients with idiopathic and diabetic gastroparesis. The role of autonomic dysfunction relating to gastric emptying and upper gastrointestinal symptoms in patients with gastroparesis and chronic unexplained nausea and vomiting (CUNV) remains unclear. The aim of our study is to evaluate autonomic function in patients with gastroparesis and CUNV with respect to etiology, gastric emptying and symptom severity. Methods: We studied 242 patients with chronic gastroparetic symptoms recruited at eight centers. All patients had a gastric emptying scintigraphy within 6 months of the study. Symptom severity was assessed using the gastroparesis cardinal symptom index. Autonomic function testing was performed at baseline enrollment using the ANX 3.0 autonomic monitoring system which measures heart rate variability and respiratory activity measurements. Key Results: Low sympathetic response to challenge (Valsalva or standing) was the most common abnormality seen impacting 89% diabetic and 74% idiopathic patients. Diabetics compared to idiopathics, exhibited greater global hypofunction with sympathetic (OR = 4.7, 95% CI 2.2‐10.3; P  < .001) and parasympathetic (OR = 7.2, 95% CI 3.4‐15.0; P  < .001) dysfunction. Patients with delayed gastric emptying were more likely to have paradoxic parasympathetic excessive during sympathetic challenge [(Valsalva or standing) 40% vs. 26%, P  = .05]. Patients with more severe symptoms exhibited greater parasympathetic dysfunction compared to those with mild‐moderate symptoms: resting sympathovagal balance [LFa/RFa 1.8 (1.0‐3.1) vs. 1.2 (0.6‐2.3), P  = .006)] and standing parasympathetic activity [0.4 (0.1‐0.8) vs. 0.6 (0.2‐1.7); P  = .03]. Conclusions: Autonomic dysfunction was common in patients with gastroparesis and CUNV. Parasympathetic dysfunction was associated with delayed gastric emptying and more severe upper gastrointestinal symptoms. Conversely, sympathetic hypofunction was associated with milder symptoms. Inferences: Gastroparesis and CUNV may be a manifestation of GI autonomic dysfunction or imbalance, such that sympathetic dysfunction occurs early on in the manifestation of chronic upper GI symptoms, while parasympathetic dysfunction results in more severe symptoms and delayed gastric emptying. Abstract : Sympathetic withdrawal (low sympathetic activity in response to a sympathetic challenge) was the most common autonomic abnormality found among all patients.